KINERJA APARATUR PEMERINTAH DALAM PEMBUATAN KARTU TANDA PENDUDUK (KTP) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANGGAI KEPULAUAN - Rizal, Syamsu (Katalogis, 2018)
The research aims to determine the competence of the individual, organizational support and management support in the improvement of performance and to determine enabling and inhibiting factors in the manufacture of identity cards (ID) in the Department of Population and Civil Registration Banggai Regency. Theory of performance used from Simajuntak (201;11-17) consists of aspects - aspects that affect the performance of employees is the competence of individual, organizational support and management support. This type of research is descriptive qualitative informant is taking the government apparatus of Population and Civil Registration and communities determined by purposive. Retrieval techniques and data collection techniques include observation, interview techniques (interview), and documentation (ducumentation),While data analysis techniques used in this study using a model of Miles and Humberman. The results showed: 1) Performance of Administrative Office of Population and Civil Registration Banggai Regency is not optimal due to the support aspect organizational are still inadequate, despite this aspect of individual competencies and management support has been optimized; 2) factors inhibiting performance Apparatus Department of Population and Civil RegistrationÂ  Banggai Regency in the manufacture of identity cards (ID) is the lack of organizational support in the form of the limited number of facilities and infrastructures such as the provision of facilities print machine and a camera that have only one (1) unit, causing a delay in the process of service so that the effect on the amount of the issuance of identity card; 3) Factors supporting performance Apparatus Department of Population and Civil Registration Banggai Regency in the manufacture of identity cards (ID) is the competence of individuals and management support. Individual competencies possessed by the apparatus is a skill, work ethic and motivation. In addition to individual competencies, enabling factors that support organizational performance management, among others, the ability of the leadership to accommodate the implementation of the activities of the organization as well as creating a conducive work environment.